Predictive modelling of the physical demands during training and competition in professional soccer players - Giménez, J. V.; Jiménez-Linares, L.; Leicht, A. S.; Gómez, M. A. (Journal of Science and Medicine in Sport, 2020)
Objectives: The present study aimed to predict the cut-off point-values that best differentiate the physical demands of training and competition tasks including friendly matches (FM), small sided games (SSG), large sided games (LSG), mini-goal games (MG) and ball circuit-training (CT) in professional soccer players.